Measles and Its Association with Blood, Organ Functions, and Growth in Children - Huntus, Zina Saleam; AL-Shwilly, Ali A. H. (Jurnal Kebidanan Midwiferia, 2025)
Measles is a febrile illness with a systemic rash disease vaccine. It raises morbidity and mortality rates globally even though a safe and efficient live attenuated vaccine is available. To evaluate the impact of measles on blood cell composition, liver and kidney functions, physical growth, and nutritional status in children during the first 14 days of infection. A cross-sectional observational study was conducted in Al-Rifai Teaching Hospital during the period from April to October 2024. The study included a convenient sample of 50 children under the age of 10 years who were diagnosed with measles. The data was collected by the researcher during the first 14 days of infection and included complete blood count, liver function test, renal function, anthropometric data measurement, and vaccination status. Regarding the haematological parameters, 24 (48%) of the patients had a low WBC count, 12 (24%) had low Hb, and 7 (14%) of them had a low platelet count. About the liver and renal function, 5 (10%) of the patients had elevated GOT, 3 (6%) had elevated GPT, 2 (%) had elevated blood urea, and 7 (14%) of them had elevated serum creatinine. Measles significantly impacts blood cell composition, liver function, and nutritional status in children. The findings underscore the importance of vaccination and the need for nutritional support during and after infection to minimize complications.